Understanding Consumer Travel Behavior during COVID-19 - Chen, Xianglan; Duan, Yachao; Ali, Laiba; Duan, Yahui; Ryu, Kisang (Mdpi, 2021)
Since the COVID-19 outbreak worldwide, the global tourism industry has taken a severe hit. To fully understand the impact of the pandemic on tourists' travel behavior, an intercultural survey was carried out through a large-scale online questionnaire. This survey aims to determine whether cultural differences and different ages might play a role in tourists' behavior during the COVID-19. Data collected from 942 respondents from mainland China and overseas through different age groups were subjected to data analysis. The results demonstrate cognition and consumer behavior differentiate culturally and significantly between different ages, which is highlighted when they choose travel modes, transportation, and companions. The implications of the study are also provided in the end.
Keywords: consumer behavior; travel behavior; COVID-19